Utilization of black rice (Oryza sativa L. indica) extract in making sarabba as functional drink - Meta Mahendradatta; Ulfa Mutmainnah Alri; Mariyati Bilang; Abu Bakar Tawali (jurnal1, 2021)
Indonesian traditional drink such as Sarabba is generally consumed for its taste. However, this drink has certain functional properties which originated from its basic ingredients. To enhance its functional properties, other natural ingredients such as black rice extract can be added to the basic ingredients. Therefore, the objectives of this study were to obtain the best treatment for the use of black rice extract in producing of Sarabba and to determine the effect of drying time on proximate value, anthocyanin, and thiamine contents; and solubility level of the product. The black rice used in this study was a local type variety that contains high amount of anthocyanins, a group of flavonoids, which is beneficial to health. Black rice was mixed with water at different ratios, grinded, and filtered. The filtrate obtained was used in formulation and the drink obtained was analyzed organoleptically. The best result of sensory evaluation based on color, taste, odor and texture was found in treatment 70% rice: 30% water. The treatment with the highest organoleptic score was used in this second stage of this study which involve drying of the Sarabba drink for 1, 1.5, and 2 hours. Proximate, anthocyanin, thiamine contents and solubility of the powder were determined. The result showed that best content of water (1.67%), carbohydrate (0.11%) and solubility level (20 seconds) were obtained at two hours drying. The best content of ash (2.3%), anthocyanin (11.83%), thiamin (0.056%) and fat (0.03) were obtained from one hour drying. The highest protein content (4.78%) was obtained from 1.5 hours drying treatment.